Insight into the esterase like activity demonstrated by an imidazole appended self-assembling hydrogelator1. Issue 67 (28th August 2015) - Singh, Nishant; Conte, Maria P.; Ulijn, R. V.; Miravet, Juan F.; Escuder, Beatriu
<x xml:space="preserve">Abstract</x> Hydrolysis of unactivated phenylalanine methyl ester by a simple imidazole appended hydrogelator is reported for the first time.